Unequal pain: a sketch of the impact of the Covid-19 pandemic on migrants' employment in China. Issue 4 (2nd September 2020) - Che, Lei; Du, Haifeng; Chan, Kam Wing
ABSTRACT: This article examines the impact of the Covid-19 pandemic on the employment of migrant workers in China. Our research has estimated that nationally, at least 30–50 million migrants lost their jobs in late March, far more than the local urban workers. An online survey also indicates that the rural- hukou population have borne the brunt of the outbreak. More than 90% rural- hukou migrant workers could not find work as of late February, compared to 42% for urban- hukou migrant workers. Those who are less educated and low skilled had also a higher rate of unemployment. At the same time, there is a serious mismatch between workers covered by the social safety net and those who really need it. Both across the Chinese population at large and within the migrant population itself, the pandemic has exacerbated the preexisting inequalities along the household registration system line. We call for a more substantive reform of the system so that migrant workers can be integrated into the national social safety net and be protected in the next crisis.